Adverse selection in the labour market and the demand for vocational education - Sonja Chen (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2016)
In this paper, I show that displacement of high-school workers from routine jobs can be understood as the labour-market response to an adverse selection problem. The adverse selection problem arises because employment contracts do not systematically discriminate against education, even though over-qualified workers are relatively more likely to quit routine jobs. The labour market equilibrium distorts the labour market outcomes of high school graduates by inefficiently increasing their wage at the expense of higher unemployment rate, in order to separate them from overqualified college graduates. In addition, the labour market response to the adverse selection problem creates a demand for post-secondary vocational education, which is valuable because it acts as an entry barrier that prevents college graduates from using routine jobs as stepping-stones towards better jobs.
Keywords: 330